Chasing the Dragon Assessing China's System of Export Controls for WMD-Related Goods and Technologies - Medeiros, Evan S. (RAND Corporation, 2005)
China's export controls on equipment, materials, and technologies used to produce weapons of mass destruction (WMD) have evolved significantly since the early 1980s. This monograph examines the structure and operation of the Chinese government's system of controls on exports that could be used in the production of WMD and WMD-related delivery systems. The author identifies the key organizations involved in export control decisionmaking, relevant laws and regulations, and the interactions among government organizations involved in vetting sensitive exports.